Male out-migration and women's work and empowerment in Agriculture: the case of Nepal - Slavchevska, Vanya (International Center for Tropical Agriculture, 2018)
Presented by Vanya Slavchevska (CIAT), as part of the Annual Gender Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Addis Ababa, 25-27 September 2018.